1987
DOI: 10.1039/f19878300167
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth alternation, as a result of intramolecular cation migration, in the electron spin resonance spectrum of the 1,4-naphthoquinone radical anion

Abstract: The radical anion of 1,4-naphthoquinone has been prepared by electrochemical reduction in dimethylformamide and by alkali-metal reduction in 1,2-dimethoxyethane. The e.s.r. spectrum of the radical anion in dimethylformamide can be readily interpreted in terms of three pairs of equivalent protons. However, in 1 ,Zdimethoxyethane, association of the alkali-metal counter-ion with one of the carbonyl groups removes the equivalence within each of these pairs. Linewidth alternation is observed in the e.s.r. spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… 39 Further, the potential binding to TA hydroxyl reaction sites 23 and the high stability of ionic (O - ···Li + ) complexes may cause irreversible Li + complexes with phenolic structures. 40 , 41 This effect is for example encountered in lithiation of the solid-state interface in energy storage materials. 42 Regarding interactions between Li + and Si aq , an interaction preventing the assembly of silicate-TA networks may also be plausible, but evidence of any reactions under the conditions of this study were not found in literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 39 Further, the potential binding to TA hydroxyl reaction sites 23 and the high stability of ionic (O - ···Li + ) complexes may cause irreversible Li + complexes with phenolic structures. 40 , 41 This effect is for example encountered in lithiation of the solid-state interface in energy storage materials. 42 Regarding interactions between Li + and Si aq , an interaction preventing the assembly of silicate-TA networks may also be plausible, but evidence of any reactions under the conditions of this study were not found in literature.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by influences in charge densities caused by the cation. 34 , 41 All salts produced lower intensities for ⧫- and ◊-radicals ( Figure S16 ). At pH 9, this effect was however canceled by Si aq for NaCl and LiCl ( Figure S16 ), which suggests a radical stabilizing effect similar to Zn 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a well-established method [3,4], spectral simulation involving the two-site jumping of cations was performed [ Fig. 1(1 ]), suggesting some effect caused by intermolecular jumping of the cation.…”
Section: Migration Of Sodium Cationmentioning
confidence: 99%
“…EPR studies of semiquinone radical anions have provided information about electron transfers, but they have been even more informative about cation migration between two sites. Until now, discussion of the mechanism of cation migration in 1,4-naphthoquinone and 2,5-di-tert-butyl-1,4-benzoquinone radical anions has been based on the EPR studies [3,4]. However, the detailed mechanism of cation migration has not yet been established.…”
Section: Introductionmentioning
confidence: 97%